Teaching Musical Disciplines: Modern Theoretical and Methodological Approaches and Principles - Husanov Rustamjon Ravshanjon ogli (Genius Journals, 2021)
The article says that the Uzbek upbringing and educational system is at a turning point in its development, it is going through one of the most difficult, dramatic episodes in its history. Naturally, everything that is associated with changes in the depths of this system, its reform, the struggle of views, theories, attitudes is of wide public interest.
Keywords: Musical discipline; methodological approach; educational system; pedagogical activity